Andrzej Rozwadowski, Obrazy z przeszłości. Hermeneutyka sztuki naskalnej, Poznań 2009 - Harat, Karolina (Folia Praehistorica Posnaniensia, 2018)
The review of A. Rozwadowski’s „Images from the Past: Hermeneutics of the Rock Art” underlines its innovative approach to the complexity of the problem presented in this study.